Matha (residential building) in the Suhaveshwar Temple Complex - Temples of India Project Team (Jio Institute, 2024)
Seen here is the north-facing façade of the residential building, a Shaiva matha from the Suhaveshwar temple complex. It is a two-storeyed structure with several rooms on both floors. The matha is in ruinous condition. The exterior stone of the matha is broken in several places.